O Pronatec e Sistemas S: o mercado da qualificação profissional - um estudo a partir do município de Ampére - PR - Silva, Juliano André Deotti da (2017)
This research analyzed the National Program of Access to Technical Learning and Employment (PRONATEC) in the form of Graduation Grants in partnership with the S System, specifically in the town of Ampére, Paraná. The object was to understand PRONATECH‘s operation and structure, especially in partnership with the S System within professional graduation social policies, figuring out how it came to be in the town of Ampére. The research has been grounded on the critical analysis of OLIVEIRA (2007), FRIGOTTO (2005), BARRADAS (1986), CUNHA (2005), NEVES; PRONKO (2008), RAMOS (2011), POCHMANN (2007), to unveil the PRONATECH policy and the partnership with the S System. From bibliographic review, it aimed at putting PRONATECH in a historical context considering the professional preparation in Brazil, from 1909 to the creation of the S System in 1940 to the Workforce Intensive Preparation Program (PIPMO) from 1961 to 1986 to the National Workforce Preparation Plan (PLANFOR) in the 1990s which lasted until 2000. We also highlighted the National Plan of Qualification (PNQ), the latter having preceded PRONATECH. Thus, it was possible to reveal how focal policies are rooted, what the main objectives are and how a program with the PRONATECH magnitude comes true in a small town, bearing in mind the social, political, and economical contexts Brazil has gone through historically. With that in mind, the research aimed at a nationwide analysis, highlighting how PRONATECH is structured, ranking all the initiatives that make up the program in the form of Graduation Grant. As far as PRONATECH is concerned, MEC‘s Control Panel data were used. Through these numbers it was possible to structure and organize the data to put the research together and have an enrollment overview in Brazil, the state of Paraná, in the microregion of the Southwest of Paraná, and in Ampére. These enrollments were identified according to age groups, sex, loan, providing networks and region, technical course types, and Continuous Beginner‘s Preparation (FIC). Finally, the research deeply analyzed PRONATECH in Ampére with semi-structured interviews of students leaving the program and getting to know if the program has helped them entering the job market, and also by showing the dropping-out numbers. The result we have reached showed that the courses offered at PRONATECH in the town of Ampére have not contributed to young people entering the job market, which, according to statements of students who left the program the drop out index has occurred more in technical courses than in FICs. Another aspect that was identified is that FIC courses do not prepare students properly due to their length.